Evolutionary origin of synapses and neurons – Bridging the gap - Burkhardt, Pawel; Sprecher, Simon G. (BioEssays, 2017)
The evolutionary origin of synapses and neurons is an enigmatic subject that inspires much debate. Non‐bilaterian metazoans, both with and without neurons and their closest relatives already contain many components of the molecular toolkits for synapse functions. The origin of these components and their assembly into ancient synaptic signaling machineries are particularly important in light of recent findings on the phylogeny of non‐bilaterian metazoans. The evolution of synapses and neurons are often discussed only from a metazoan perspective leaving a considerable gap in our understanding. By taking an integrative approach we highlight the need to consider different, but extremely relevant phyla and to include the closest unicellular relatives of metazoans, the ichthyosporeans, filastereans and choanoflagellates, to fully understand the evolutionary origin of synapses and neurons. This approach allows for a detailed understanding of when and how the first pre‐ and postsynaptic signaling machineries evolved. The evolutionary origin of synapses and neurons is an enigmatic subject that inspires much debate. Most of our knowledge and recent discussions are biased towards a metazoan perspective, leaving a considerable gap in our understanding. Recent work has now revealed important insights into the emergence and co‐regulation of complex synaptic signaling machineries from studies in the closest unicellular relatives of metazoans (choanoflagellates, filastereans, and ichthyosporeans).